Existência de pontos críticos de funcionais definidos em espaços de Banach via método da variedade de Nehari - Sanches, Juliana Mancini (2020)
In this work we present a unified approach about the method of Nehari manifold for functionals which have a local minimum at 0 and we do some examples where this method is applied in order to get ground states and multiple solutions for nonlinear elliptic boundary value problems.